Future anxiety and its relationship to mental health among a sample of Bouira University students - Harizi BOUDJEMAA (Social Sciences Journal, 2023)
This study aimed to identify the relationship between future anxiety and mental health among a sample of Bouira University students, and in order to achieve this objective, the study was using the relational descriptive approach, and the sample was chosen randomly, and it consisted of (50) male and female students, and two tools were used in the study: The Future Anxiety Scale, and the Mental Health Scale.The results of the study showed that the level of future anxiety among a sample of Bouira University students is high, and that their level of mental health is average, and that the correlation positive and statistically significant between future anxiety and their mental health.